Battling terrorism in the Horn of Africa - Rotberg, Robert I.; World Peace Foundation; Brookings Institution (Cambridge, Mass. : World Peace Foundation ; Washington, D.C. : Brookings Institution Press, 2005)
"Examines the state of governance in the countries of the greater Horn of Africa region--Djibouti, Eritrea, Ethiopia, Kenya, Somalia, the Sudan, and Yemen--and discusses strategies to combat the transnational threat of terrorism, including suggestions for more effective U.S. engagement in the region"--Provided by publisher.
The Horn of Africa and Yemen : diminishing the threat of terrorism / Robert I. Rotberg -- Somalia and Somaliland : terrorism, political Islam, and state collapse / Kenneth J. Menkhaus -- Djibouti : a special role in the war on terrorism / Lange Schermerhorn -- Eritrea : on a slow fuse / Dan Connell -- Ethiopia : governance and terrorism / David H. Shinn -- The Sudan : political Islam and terrorism / Timothy Carney -- Yemen : its political economy and the effort against terrorism / Robert D. Burrowes -- Kenya : the struggle against terrorism / Johnnie Carson.
Includes bibliographical references and index.
Keywords: Terrorism -- Horn of Africa -- Prevention; Islam and politics -- Horn of Africa